2014
DOI: 10.1016/j.actatropica.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi nucleoside triphosphate diphosphohydrolase 1 (TcNTPDase-1) biochemical characterization, immunolocalization and possible role in host cell adhesion

Abstract: Previous work has suggested that Trypanosoma cruzi diphosphohydrolase 1 (TcNTPDase-1) may be involved in the infection of mammalian cells and serve as a potential target for rational drug design. In this work, we produced recombinant TcNTPDase-1 and evaluated its nucleotidase activity, cellular localization and role in parasite adhesion to mammalian host cells. TcNTPDase-1 was able to utilize a broad range of triphosphate and diphosphate nucleosides. The enzyme's Km for ATP (0.096 mM) suggested a capability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
5
20
0
Order By: Relevance
“…These results suggested the existence of a possible binding site (like an unknown receptor) for the Lic-E-NTPDase2 in macrophages that could participate in facilitating adhesion and infection [46] . These data are in accordance with previous results also observed in T. cruzi [45] . [80] .…”
Section: Biochemical and Biological Roles Of Ecto-nucleotidases And Tsupporting
confidence: 83%
See 2 more Smart Citations
“…These results suggested the existence of a possible binding site (like an unknown receptor) for the Lic-E-NTPDase2 in macrophages that could participate in facilitating adhesion and infection [46] . These data are in accordance with previous results also observed in T. cruzi [45] . [80] .…”
Section: Biochemical and Biological Roles Of Ecto-nucleotidases And Tsupporting
confidence: 83%
“…There is a direct relationship between the ability to hydrolyze nucleotides and the ability to sustain infection [39, 42-44, 47, 74, 78, 115-119] . It has also been shown recently that the E-NTPDase of parasites can act as an adhesion protein during the early stages of infection [45,46,120] . Inhibiting Leishmania molecules that actively modulate the macrophage signaling pathways is essential to prevent the intracellular survival of Leishmania.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, studies have suggested a role of carbohydrate/lectin interactions on T. rangeli adhesion on insect salivary glands (Basseri et al, 2002;Mello et al, 1999). Interestingly, evidences suggested that T. cruzi NTPDase is possibly involved in host cell adhesion (Mariotini-Moura et al, 2013) and previous studies have showed a plant NTPDase/lectin byfunctional protein that is activated by the presence of carbohydrates (Etzler et al, 1999) . Based on these evidences, researchers have previously investigated the role of carbohydrates on T. rangeli NTPDAse activity.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that distinct ecto-enzymes could contribute to the parasite adaptation to stress conditions, as nutrients starvation or heat shock. Recently, Mariotini-Moura et al [24] performed heterologous expression, purification and molecular characterization of TcNTPDase-1. By using specific polyclonal antibodies, they confirmed the presence of TcNTPDase-1 not only on the surface of T. cruzi, but also in the kinetoplast, nucleus, intracellular vesicles, flagellum and flagellum insertion region.…”
Section: Resultsmentioning
confidence: 99%